CARDIAL-MS (CArdio-Renal-DIAbetes-Liver-Metabolic Syndrome): a new proposition for an integrated multisystem metabolic disease - Amélio F. Godoy-Matos; Cynthia Melissa Valério; Wellington S. Silva Júnior; João Marcello de Araujo-Neto; Andrei C. Sposito; José Hermógenes Rocco Suassuna (Diabetology & Metabolic Syndrome)
Abstract Background Metabolic Syndrome—a constellation of insulin resistance, cardiovascular risk factors as hyperglycemia, hypertension, and dyslipidemia, and systemic metabolic dysfunction—may be driven by dysregulation of adipose tissue, which manifests as adiposopathy (pathogenic adipose tissue expansion or maldistribution), ectopic fat deposition (in the liver, muscle, pancreas, and cardiorenal systems), and altered secretion of adipokines/hepatokines. Weight gain, obesity, and/or unfavorable fat distribution create a scenario wherein the type, size, location, secretions, or even scarcity of adipocytes drive pathophysiological mechanisms leading to hepatic steatosis and steatohepatitis, type 2 diabetes, and heart and kidney disease. While recent frameworks, such as cardiovascular-kidney-metabolic syndrome, emphasize holistic staging, the central role of metabolic dysfunction-associated steatotic liver disease (MASLD) in multisystem morbidity remains underrecognized. Main text This narrative review synthesizes evidence linking MASLD and diabetes to cardiovascular and kidney diseases through shared pathways of adiposopathy, ectopic lipid accumulation, and dysregulated adipokine/hepatokine signaling. We propose CARDIAL-MS (CArdio-Renal-DIAbetes-Liver-Metabolic Syndrome), an expanded pathophysiological model that unifies these interactions into four progressive stages: (1) weight gain and dysfunctional adipose tissue; (2) metabolic risk factors and markers of risk; (3) cardiometabolic diseases and chronic kidney disease; and (4) advanced cardio-renal-liver-metabolic disease. By integrating MASLD as a pivotal component, CARDIAL-MS reframes metabolic syndrome as a continuum of interconnected organ injuries rather than isolated risk factors. Conclusion CARDIAL-MS provides a staging model to identify patients at critical transition points—from reversible metabolic disturbances to irreversible organ damage. This model emphasizes early interventions targeting adipose tissue health and ectopic fat deposition to mitigate the progression of metabolic cardiorenal diseases. By recognizing the syndromic nature of these conditions, CARDIAL-MS offers clinicians an actionable paradigm for risk stratification, timely diagnosis, and personalized prevention strategies.